Lymphocyte and macrophage responses after vaccinia virus infections. - McLaren, C (1976)
Using a semimicromethod with washed whole blood, in vitro lymphocyte responses of rabbits to intradermal infection with vaccinia virus was studied. Peritoneal exudate macrophages were infected with vaccinia in vitro to determine the time of appearance of activated macrophages. After primary infection, an increase in spontaneous incorporation of thymidine by blood cultures was found as early as 2 days postinfection. This effect was at a maximum at 7 to 10 days, with counts up to 100-fold higher than before infection. Incubation of these cultures with concanavalin A showed a marked decrease in stimulation index as compared with normals. Although only a transient stimulation with vaccinia was found during the acute infection, stimulation indexes of 2 to 3 were obtained during convalescence. Macrophages from rabbits early after infection supported vaccinia replication, whereas those at day 6 or later resisted infection. Macrophage resistance persisted for 2 to 3 weeks. The response of lymphocytes from rabbits reinfected with vaccinia after 15 weeks differed, with a small increase in spontaneous thymidine uptake, a smaller depression in concanavalin A stimulation, and a greater specific response to vaccinia. Macrophage activation occurred earlier and persisted for a longer time after secondary infection.